Extracellular Vesicles and Their Associated miRNAs as Potential Biomarkers in Intracranial Aneurysm - Li, Yuman; Wen, Jiahao; Liang, Dingyue; Sun, Haitao (Frontiers in Molecular Biosciences, 2022)
Intracranial aneurysm is an abnormal expansion of intracranial arteries. Once it ruptures, the mortality and disability rate are high. Because imaging examinations are relatively expensive and the risk of rupture cannot be predicted, it is difficult to screen high-risk groups and prevent rupture. Therefore, clinically effective biomarkers are needed to screen high-risk groups and assess the risk of rupture, and take relevant measures for early intervention. This review introduces the current research and application of exosome-derived miRNA as biomarkers of intracranial aneurysms and their limitations, which can give relevant researchers a general understanding of the research in this field. It can also provide some reference for the selection of related research directions.